Use of bronchoalveolar lavage in the evaluation of methotrexate lung disease. - Akoun, G M (1987)
The results of bronchoalveolar lavage in three patients with a presumptive diagnosis of methotrexate induced lung disease are presented. Lavage fluid was characterised by the presence of large numbers of lymphocytes, which in two patients were predominantly lymphocytes of the T8 phenotype. These findings further support the hypothesis that immune mediated mechanisms may play a part in the pathogenesis of this disorder in some patients, and indicate that bronchoalveolar lavage may be helpful in the evaluation of patients suspected of having methotrexate induced lung disease.